Intercultural Communication Dynamics In Islamic Higher Education: An Focused Ethnographic Study At Uin K.H. Abdurrahman Wahid Pekalongan - Roisna Kamila; Nur Khotimah; Ahmad Isa Abdallah; Tegar Dwi Wibowo (Institut Bahri Asyiq Galis Bangkalan, 2025)
This study explores the dynamics of communication and learning between local and international students in a multicultural classroom at UIN K.H. Abdurrahman Wahid Pekalongan. The research was conducted to understand how linguistic differences, cultural background, and classroom interaction patterns shape learning experiences in an Islamic higher education context. Using a qualitative educational ethnography design, data were collected through participant observation and in-depth interviews with both local and international students who interacted intensively in the same class. The findings reveal that language is the primary factor influencing comprehension and participation, with international students experiencing significant challenges when Indonesian is used as the medium of instruction. Despite these barriers, communication remains effective through bilingual discussions, clarification strategies, and peer support. The class environment, characterized by open discussions, presentations, and supportive responses from lecturers and peers, fosters a sense of inclusion for all students. The study concludes that communication dynamics in this multicultural classroom operate positively, as students adopt adaptive linguistic strategies and collaborative learning practices that enable them to overcome cultural and linguistic differences. These dynamics generate an inclusive learning environment that benefits both local and international students.